Analisis Pengaruh Dompet Digital dan Cashback Terhadap Perilaku Keuangan Konsumen di E-Commerce : Studi Kasus Shopeepay dan DANA pada Pengguna Usia 18-25 Tahun di Kota Bandung (Jurnal Riset Manajemen dan Akuntansi, 2025)
This research aims to analyze the influence of digital wallet usage and cashback programs on the financial behavior of e-commerce consumers aged 18-25 years in Bandung City, focusing on ShopeePay and DANA platforms. The study employs a quantitative method with a questionnaire survey involving 77 active digital wallet users. The data were analyzed using multiple linear regression after validity, reliability, and classical assumption tests. The results show that digital wallet usage and cashback simultaneously have a significant effect on consumer financial behavior, with digital wallet usage having a more dominant partial influence.Transaction convenience and cashback incentives encourage consumptive behavior, especially among young people who are sensitive to promotions. However,weaknesses in financial management were found due to the low utilization of financial management features in digital wallet applications. This research recommends improving digital financial literacy so that young people can use digital wallets and cashback wisely and responsibly.